A Systematic Review of Psychological and Pharmacological Treatments for Adjustment Disorder in Adults. Issue 3 (29th June 2018) - O'Donnell, Meaghan L.; Metcalf, Olivia; Watson, Loretta; Phelps, Andrea; Varker, Tracey
Abstract: Adjustment disorder is a common psychiatric disorder, yet knowledge of the efficacious treatments for adjustment disorder is limited. In this systematic review, we aimed to examine psychological and pharmacological interventions that target adjustment disorder in adults to determine which interventions have the best evidence for improving adjustment disorder symptoms. We performed database searches for literature published between January 1980 and September 2016 and identified studies that included both a sample majority of individuals diagnosed with adjustment disorder and findings on adjustment disorder symptom outcomes. There were 29 studies that met the inclusion criteria for qualitative synthesis; the majority of studies (59%) investigated psychological therapies rather than pharmacological treatments (35%). The range of psychological therapies tested was diverse, with the majority containing cognitive behavioral therapy (CBT) components (53%), followed by three studies that were psychodynamic‐related, three studies that were behavioral therapy–based, and two studies that involved relaxation techniques. We rated individual studies using a modified National Health and Medical Research Council quality and bias checklist and then used the Grading of Recommendations Assessment, Development and Evaluation (GRADE; Grade Working Group, 2004) system to rate the overall quality of the evidence. Despite several randomized controlled trials, the quality of the evidence for positive effects of all psychological and pharmacological treatments on symptoms of adjustment disorder was ranked as low to very low. Future high‐quality research in the treatment of adjustment disorder has the potential to make a significant difference to individuals who struggle to recover after stressful events.